Longitudinal Improvements in Viral Suppression for Persons With New HIV Diagnosis Receiving Care in the Ryan White Program: A 10-Year Experience in New Haven, CT (2009–2018). (14th April 2022) - Zhao, Alice; Rizk, Christina; Zhao, Xiwen; Esu, Arit; Deng, Yanhong; Barakat, Lydia; Villanueva, Merceditas
Abstract: Background: The Ryan White (RW) program funds medical and other support services for low-income persons with HIV, significantly improving progress along the HIV care continuum. Although the program has shown overall improvements in achievement of viral suppression, the relative contributions of changes in clinical practice and RW service components to the optimization of the HIV care continuum, particularly for those with new HIV diagnoses, remain unknown. Methods: The target population was patients with recent HIV diagnoses who received care at RW-funded clinics in the greater New Haven area between 2009 and 2018. Client data were extracted from the RW-funded database, CAREWare, and the electronic medical record. Primary outcomes included time between HIV diagnosis and first HIV primary care (PC) visit, antiretroviral therapy (ART) initiation, and viral suppression (VS). Results: There were 386 eligible patients. Between 2009 and 2018, the median number of days from HIV diagnosis to first PC visit decreased from 58.5 to 8.5 days, and ART initiation decreased from 155 to 9 days. In 2018, 86% of participants achieved viral suppression within 1 year, compared with 2.5% in 2009. Patients who initiated single-tablet ART and integrase inhibitor–containing regimens were more likely to reach viral suppression within 1 year ( P < .001). Receipt of medical case management services was also associated with achieving viral suppression ( P < .001). Conclusions: Longitudinal improvements over 10 years in ART initiation and viral suppression were observed due to clinical advances and their effective implementation through the RW comprehensive care model. Further study of the essential components promoting these outcomes is needed.